Inviscid incompressible limit for compressible micro-polar fluids. (March 2022) - Caggio, Matteo
Abstract: In this paper we study the incompressible inviscid limit for a compressible micro-polar model. We prove that the weak solution of the compressible micro-polar system converges to the solution of the Navier–Stokes equations (Euler equations) in the limit of small Mach number (and vanishing viscosity).